Pengaruh Beban Kerja, Kompensasi, Keselamatan dan Kesehatan Kerja terhadap Kinerja Karyawan Bagian Pengolahan Kayu pada PT. Wahyu Daya Mulia - Fathonah Al Hadromi (Syntax Corporation Indonesia, 2024)
The purpose of the research was to test and analyze the effect of workload on the performance of employees of the wood processing department of PT. Revelation of Noble Power. This research is classified as explanatory research, which is testing based on theoretical and empirical studies. This research method will explain the relationship between variables by conducting a hypothesis test. It can be concluded that the workload (X1) has a positive and significant influence on performance (Y), indicating that the more appropriate and adequate the workload, the performance will increase. Nevertheless, employee perception shows that overall workload indicators are only sufficient, even if working conditions are perceived as good. Furthermore, compensation (X2) also has a positive and significant effect on performance (Y), indicating that the morefair and worthy of compensation, the performance will increase.